1978
DOI: 10.2190/xubh-uq2n-ujnf-cv88
|View full text |Cite
|
Sign up to set email alerts
|

Family Therapy with Adolescent Drug Abusers: A Review

Abstract: The purpose of this paper is to present a brief review of literature concerning the current status of family therapy in the treatment of drug abusing adolescents. The method of approach was to survey and summarize findings and statements found in the literature. The paper includes six topical areas: Why Treat the Family, Family Life of the Abuser, Approaches to Treatment, The Treatment Process, Treatment Goals, and The Treatment Program. A brief concluding statement is included expressing the need for a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Although reporting no empirical data, the reviews of Baither (1978) and Rueger and Lieberman (1984) also emphasize the potential of family therapy for substance-abusing adolescents. Similarly, Stanton (1979c) compared the treatment modalities and results of 68 studies of family interventions for substance abuse and reported that, although many methodological weaknesses exist, family treatment "shows great promise as a way of conceptualizing and intervening toward positive change" (p. 268).…”
Section: The Integrative Modelmentioning
confidence: 99%
“…Although reporting no empirical data, the reviews of Baither (1978) and Rueger and Lieberman (1984) also emphasize the potential of family therapy for substance-abusing adolescents. Similarly, Stanton (1979c) compared the treatment modalities and results of 68 studies of family interventions for substance abuse and reported that, although many methodological weaknesses exist, family treatment "shows great promise as a way of conceptualizing and intervening toward positive change" (p. 268).…”
Section: The Integrative Modelmentioning
confidence: 99%
“…Family therapy has also been used with adolescents (Bruggen and Graham, 1977;Schimel, 1979) involving drug abuse (Baither, 1978), juvenile offending (Robinson, 1978), anorexia nervosa (Caille, Abrahamsen, Girolami, and Sorbye, 1977;Minuchin, Rosman and Baker, 1978) and those labelled psychiatrically disturbed such as psychiatric inpatients (Reiss, Costell, Jones, and Berkman, 1980) and borderline adolescents (Zinner, 1978), those exhibiting bizarre behaviours (Scheiner and Musette, 1979), and even for adolescents with extreme itching (Lantz, 1979).…”
Section: For Whom Does It Work and For What Kinds Of Problems?mentioning
confidence: 99%